SPECTRUM OF MANDIBULAR FRACTURES AT A TERTIARY CARE DENTAL HOSPITAL IN LAHORE - Abbas, Iram; Ali, Kamran; Mirza, Yaqoob Baig (Journal of Ayub Medical College Abbottabad, 2003)
Background: Mandible being the only mobile bone of the facial skeleton plays a major role in mastication, speech and deglutition. Among the maxillofacial trauma, mandible is the high risk exponent. Its fractures result in severe loss of function and disfigurement. The increased vehicular accidents, conditions of our roads and other assaults have focused attention in recent years to prevent injuries. Method: A descriptive case series of 126 patients with mandibular fractures attending a tertiary referral centre over a six-month period is presented. Data concerning the patients' demographics, aetiology and pattern were obtained and analysed. Results: Approximately 56% of the patients sustained fractures from road traffic accidents and 34% of the fractures occurred in the 21-30 year age range. There was a male preponderance with a male to female ratio of 9:1. Parasymphyseal fractures were the most common followed by those of the condylar and subcondylar regions. Conclusions: We need to encourage further research work in this field to provide better record keeping and quality of services to the injured people. Amendments in the traffic rules and legislation about seat-belt usage and traditional kite flying to reduce frequency of fractures are required. Key Words: Mandibular Fractures, Facial Skeleton Fractures, Seat Belts